Literasi Digital Akuntansi: Menyiapkan Siswa SMK sebagai Talenta Muda di Era Artificial Intelligence - Kristianto, Giovanny; Saraswati, Esti; Istiningrum, Farida (Apik Cahaya Ilmu, 2025)
The advancement of digital technology and artificial intelligence (AI) has significantly transformed the landscape of the accounting profession, demanding new skill sets from vocational education graduates, including vocational high school (SMK) students. This Community Service Program aims to enhance the digital literacy of students at SMK Al Fatah Banjarnegara through outreach and training on digitalization and the application of AI in accounting. The methods employed include interactive seminars, group discussions, and the introduction of digital accounting software. The outcomes of the program indicate an improved understanding among students regarding the concept of digitalization, as well as a growing interest in exploring technology-based accounting more deeply. This initiative serves as an initial step in bridging the gap between the vocational school curriculum and industry demands, while also fostering a vocational learning ecosystem that is responsive to digital transformation. It is expected that this program will continue through technical training, module development, and curricular collaboration between universities and vocational schools